PROFESSIONAL LIABILITY IN SELECTED MEDICAL PROFESSIONS - Jacek, Anna; Ożóg, Katarzyna (Review of European and Comparative Law, 2020)
To sum up, professional liability is an additional mode of responsibility, not included in the common law. Professional liability occurs when medical personnel violate provisions on the practice of the profession or act against the rules of professional ethics. Professional responsibility is borne for a breach of the principles of medical ethics or provisions relating to the practice of medical profession. Medical personnel may be punished for professional misconduct by: admonition, reprimand, prohibition on holding managerial positions in organizational health care entities for a period from one to five years, prohibition on holding a position of one’s choice in the bodies of self-government for the period from one to five years, limitation on activities within the profession for a period from six months to two years, suspension of the right to practice the profession for a period from one to five years, deprivation of the right to practice the profession. A doctor and dentist have the right to appeal against the decision of the Medical Court at II instance in any case, regardless of the imposed punishment. A nurse and midwife may appeal against the decision of the Supreme Court of Nurses and Midwives only in the case the penalty of suspension or deprivation of the right to practice the profession. There is a widespread opinion that it is very difficult for a victim to get a positive outcome in the medical courts, even in the cases of obvious medical errors or negligence.